Serving with Heart: How Responsive Empathy and Interpersonal Communication Change Customer Satisfaction in Customer Service of Telecommunication Services? - Rina Marlina; Rini Agustin; Nur Hayati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to see how responsiveness, empathy, and interpersonal communication impact customer satisfaction in telecommunication services. This study uses a quantitative approach, using regression analysis to see how these variables relate. The results show that responsiveness has a positive and significant influence on customer satisfaction, which means that the level of customer satisfaction will increase along with how quickly and appropriately a company handles customer complaints and requests. However, empathy and interpersonal communication do not significantly affect customer satisfaction, indicating that customers prioritize functional aspects such as the speed and accuracy of responses to complaints. Therefore, telecommunications needs to improve service responsiveness by utilizing digital technologies such as AI-based chatbots and integrated information systems. In addition, although empathy and interpersonal communication do not have a direct effect, it is still important to build good interactions to increase customer loyalty in the long run. Companies.